ANALYSIS OF METANIL YELLOW IN PACKAGED JAMU BY UV-VIS SPECTROPHOTOMETRIC METHOD - Lestari, Sri; Pramushinta, Intan Ayu Kusuma; Sinulingga, Amanda Safithri (jfpublisher, 2024)
Introduction. Metanil yellow is a synthetic coloring material used for textile products, wood paint, painting paint, and fur. Despite its use having been banned in the Regulation of the Minister of Health of Indonesia No. 239/MENKES/PER/V/1985, metanil yellow is still commonly found in the local community. In Indonesia, this coloring material is often misused to color various types of food, including herbs, crackers, noodles, tofu, and yellow snacks. The purpose of this research is to validate the analytical method for determining metanil yellow levels in herbal medicine of jamu using the UV-Vis spectrophotometric method. Method. In this research, the determination of metanil yellow levels was carried out by instrument analysis using the UV-Vis Sectrophotometric method. Result & Analysis. In the linearity validation parameter, the regression equation y = 0.0548x-0.01398 is obtained with an r² value of 0.9999, the LOD parameter is 0.11686 ppm, LOQ is 0.5620 ppm, the precision parameter RSD value obtained is 0.87% which meets the requirements of ≤ 4%. Furthermore, the results on the determination of metanil yellow levels in each sample A obtained a percentage of 0.00006755% ± 3.9260; sample B obtained a percentage of 0.000110% ± 10.5309; and sample C obtained a percentage of 0.0001023% ± 9.2998. Discussion. Given the very low concentration, it is possible that the yellow color in the herbal medicine samples is not completely caused by metanil yellow, but it might also be influenced by other natural ingredients with yellow pigments.